Benralizumab Depletes IL‐5Rα‐Bearing Cells in Skin Lesions of Patients With Atopic Dermatitis - Christiane E. Whetstone; Ruth P. Cusack; Emma L. Price; Karen J. Howie; Caitlin Stevens; Dhuha Al‐Sajee; Suzanne Beaudin; Jennifer Wattie; Nadia Alsaji; Abbey Schlatman; Vanessa Luk; Paul M. O'Byrne; et al. (Clinical and Translational Allergy)
ABSTRACT Background Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by tissue eosinophilia and itch. We evaluated the effect of eosinophil depletion with benralizumab on markers of inflammation in the skin of patients with AD. Methods After a 4‐week washout from oral anti‐inflammatory medications 20 patients with moderate to severe AD completed a randomized, double‐blind, placebo‐controlled parallel‐group study comparing 3 doses q4wk 30 mg subcutaneous benralizumab to placebo. Lesional and unaffected skin biopsies were collected before and after 28 and 65 days of treatment, respectively, for quantification of eosinophils and IL‐5Rα‐bearing cells in papillary dermis. Histological measurements of epidermal thickness, spongiosis, neutrophilic and lymphocytic infiltration, as well as clinical scores EASI, SCORAD, IGA, DLQI, and POEM were conducted throughout the study. Outcomes were compared between placebo and benralizumab treatment groups using a Mann‐Whitney U‐test. Results Benralizumab, compared to placebo, reduced IL‐5Rα+ cells and MBP+ EG2+ eosinophils in lesions and unaffected skin (p < 0.05). In skin lesions, benralizumab reduced MBP+ eosinophils and basophils but had no effect on eosinophil progenitor (EoP; CD34+ IL‐5Rα+) or mast cell numbers. There was no change in other skin histological measurements or IGA scoring of the observational lesion, nor improvement in clinical scores. Conclusion Benralizumab treatment significantly inhibited accumulation of MBP+ eosinophils and basophils in lesional skin of patients with moderate to severe AD. However, a lack of improvement in histological and clinical outcomes suggests that other inflammatory pathways are central to the pathobiology of severe atopic dermatitis. Trial Registration (ClincialTrials.gov number, NCT03563066)